Optimal cardiac strategy based on the history of myocardial infarction in type 2 diabetic patients with coronary artery disease - Tsujimoto, Tetsuro (Sci Rep, 2019)
The aim of this study was to evaluate the association between the cardiac treatment strategy and cardiac event risk in type 2 diabetic patients with coronary artery disease (CAD) based on the history of myocardial infarction. Using Bypass Angioplasty Revascularization Investigation 2 Diabetes (BARI 2D) trial data, a Cox proportional hazard model was used for calculating hazard ratios (HRs) for major cardiac events in patients receiving early revascularization or intensive medical therapy. Patients without (n = 1,557) and with myocardial infarction (n = 736) were separately analyzed. In patients without myocardial infarction, risk of major cardiac events was similar for percutaneous coronary intervention and intensive medical therapy groups, whereas it was significantly lower in the coronary artery bypass grafting group than in the intensive medical therapy group (HR: 0.48, 95% confidence interval [95%CI]: 0.30–0.76, P = 0.002). Conversely, in patients with myocardial infarction, risk of major cardiac events was significantly higher in the early revascularization group than in the intensive medical therapy group (HR: 1.47, 95%CI: 1.03–2.11, P = 0.03). In type 2 diabetic patients with CAD, benefits of early revascularization were observed only in those without previous myocardial infarction. For patients with previous myocardial infarction, intensive medical therapy exerted superior benefits.